Peripheral blood stem cell versus bone marrow graft for patients ≥60 years undergoing reduced intensity conditioning haploidentical transplantation for acute myeloid leukemia in complete remission: An analysis of the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Devillier, Raynier; Galimard, Jacques-Emmanuel; Blaise, Didier; Raiola, Anna Maria; Bramanti, Stefania; Grillo, Giovanni; Pastano, Rocco; de Latour, Régis Peffault; Busca, Alessandro; López-Corral, Lucía; Rodríguez, Arancha Bermúdez; Schmid, Christoph; et al. (American journal of hematology, 2024)
In the context of T-cell replete haploidentical stem cell transplantation (Haplo-SCT) using post-transplantation cyclophosphamide (PT-Cy), it is still unknown whether peripheral blood (PB) or bone marrow (BM) is the best graft source. While PB is associated with a higher incidence of graft-versus-host disease (GVHD), it may induce a stronger graft-versus-leukemia effect compared to BM, notably in acute myeloid leukemia (AML). From the EBMT registry database, we compared T-cell replete PB (n = 595) versus BM (n = 209) grafts in a large cohort of 804 patients over the age of 60 years who underwent Haplo-SCT with PT-Cy for an AML in first or second complete remission. The risk of acute GVHD was significantly higher in the PB group (Grade II-IV: HR = 1.67, 95% CI [1.10-2.54], p = 0.01; Grade III-IV: HR = 2.29, 95% CI [1.16-4.54], p = 0.02). No significant difference was observed in chronic GVHD or non-relapse mortality. In the PB group, the risk of relapse was significantly lower in the PB group (HR = 0.65, 95% CI [0.45-0.94], p = 0.02) and leukemia-free survival was significantly better (HR = 0.76, 95% CI [0.59-0.99], p = 0.04), with a trend toward better overall survival (HR = 0.78, 95% CI [0.60-1.01], p = 0.06). We conclude that in the specific context of Haplo-SCT with PT-Cy, PB grafts represent a valid option to decrease the risk of relapse and improve outcome of older AML patients who usually do not benefit from conditioning intensification.
Keywords: indukce remise; Cyclophosphamide; cyklofosfamid; Leukemia, Myeloid, Acute; Humans; příprava pacienta k transplantaci; lidé středního věku; haploidentická transplantace; Middle Aged; akutní myeloidní leukemie; Europe; Registries; Remission Induction; mužské pohlaví; Transplantation Conditioning; Transplantation, Haploidentical; transplantace kostní dřeně; Bone Marrow Transplantation; nemoc štěpu proti hostiteli; Evropa; registrace; transplantace periferních kmenových buněk; Pathologic Complete Response; ženské pohlaví; Peripheral Blood Stem Cell Transplantation; lidé; Graft vs Host Disease; patologická kompletní odpověď; Aged; senioři; Male; Female